Straits Settlements vol.68-69 (Great Britain : Public Record Office, 1971)
Mengandungi sambungan kepada'Blue Book for the year 1918';'Straits Settlements. Return of imports and exports during the year 1918';'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements from and to other Countries in 1917 and 1918; 1918 and 1919';'Return of imports and exports for the year 1919'.